Axillary Imaging Following a New Invasive Breast Cancer Diagnosis—A Radiologist's Dilemma. Issue 6 (2nd November 2021) - Dialani, Vandana; Dogan, Basak; Dodelzon, Katerina; Dontchos, Brian N; Modi, Neha; Grimm, Lars
Abstract: Traditionally, patients with newly diagnosed invasive breast cancer underwent axillary US to assess for suspicious axillary lymph nodes (LNs), which were then targeted for image-guided needle biopsy to determine the presence of metastasis. Over the past decade, there has been a shift towards axillary preservation. For patients with palpable lymphadenopathy, the decision to perform axillary imaging with documentation of the number and location of abnormal LNs in preparation for image-guided LN sampling is straightforward. Since LN involvement correlates with cancer size, it is reasonable to image the axilla in patients with tumors larger than 5 cm; however, for tumors smaller than 5 cm, axillary imaging is often deferred until after the tumor molecular subtype and treatment plan are established. Over the last decade, neoadjuvant chemotherapy (NACT) is increasingly used for smaller cancers with more aggressive molecular subtypes. In most cases, detecting axillary metastasis is critical when deciding whether the patient would benefit from NACT. There is increasing evidence that abnormal axillary US findings correlates with LN metastases and reliably establishes a baseline to monitor response to NACT. Depending on hormone receptor status, practices may choose to image the axilla in the setting of clinical stage T1 and T2 cancers to evaluate nodal status and help determine further steps in care. Radiologists should understand the nuances of axillary management and the scope and challenges of LN marking techniques that significantly increase the precision of limited axillary surgery.